2020
DOI: 10.1017/s0272263120000467
|View full text |Cite
|
Sign up to set email alerts
|

Domain-General Auditory Processing Explains Multiple Dimensions of L2 Acquisition in Adulthood

Abstract: In this study, we propose a hypothesis that domain-general auditory processing, a perceptual anchor of L1 acquisition, can serve as the foundation of successful post-pubertal L2 learning. This hypothesis was tested with 139 post-pubertal L2 immersion learners by linking individual differences in auditory discrimination across multiple acoustic dimensions to the segmental, prosodic, lexical, and morphosyntactic dimensions of L2 proficiency. Overall, auditory processing was a primary determinant of a range of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…All in all, our findings concur with the mounting empirical evidence that auditory processing is a determinant of how much L2 learners can benefit from immersion experience, resulting in more advanced outcomes (Saito & Tierney, forthcoming), and the theoretical view that the same driving faculty of L1 acquisition (i.e., auditory processing) is tied to every stage of L2 acquisition throughout an individual's lifetime (Flege, 2018). Building on the prior work (e.g., Saito et al, 2020 for segmental and suprasegmental production), we add that such audition effects are more clearly observed not only in the acquisition of relatively difficult features (accuracy rather than fluency, breadth, and abstractness), but also in the dimensions more closely related to the speech signal (phonology rather than lexicogrammar). Interestingly, hearing research has shown that auditory deficits can be remedied via focused training (e.g., Carcagno & Plack, 2011 for 10 hours of pitch discrimination training).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All in all, our findings concur with the mounting empirical evidence that auditory processing is a determinant of how much L2 learners can benefit from immersion experience, resulting in more advanced outcomes (Saito & Tierney, forthcoming), and the theoretical view that the same driving faculty of L1 acquisition (i.e., auditory processing) is tied to every stage of L2 acquisition throughout an individual's lifetime (Flege, 2018). Building on the prior work (e.g., Saito et al, 2020 for segmental and suprasegmental production), we add that such audition effects are more clearly observed not only in the acquisition of relatively difficult features (accuracy rather than fluency, breadth, and abstractness), but also in the dimensions more closely related to the speech signal (phonology rather than lexicogrammar). Interestingly, hearing research has shown that auditory deficits can be remedied via focused training (e.g., Carcagno & Plack, 2011 for 10 hours of pitch discrimination training).…”
Section: Discussionsupporting
confidence: 89%
“…According to the prosodic account of L2 grammar (Goad & White, 2019), the accurate encoding of prosodic cues is believed to be a necessary AUDITORY PROCESSING & VOCABULARY condition for the acquisition of complex morphology (e.g., inflection), syntax (e.g., word order), and semantics (e.g., articles). Thus, we hypothesize that individual differences in pitch, duration, and amplitude rise time may determine the extent to which learners can extract L2 morphosyntactic information from aural input and that those with more precise prosodic processing can demonstrate more advanced L2 morphosyntactic proficiency (e.g., Kachlicka et al, 2019;Saito et al, 2020).…”
Section: Domain-general Auditory Processing In L2 Acquisitionmentioning
confidence: 99%
“…The conclusion here generally concurs with the existing short‐term training literature showing auditory processing facilitates the process and product of novel language learning (e.g., Wong & Perrachione, 2007). This conclusion is in line with emerging research showing that auditory processing matters for the acquisition of the relatively difficult aspect of L2 speech acquisition in naturalistic settings (i.e., accuracy rather than fluency; Saito et al., 2020a; Saito et al., in press).…”
Section: Discussionsupporting
confidence: 88%
“…In such contexts, for the efficient and effective processing of every input opportunity, learners rely on both auditory integration (converting input into motor action) and acuity (conducting fine‐grained analyses of input). Thus, those with more precise auditory processing can demonstrate various dimensions of advanced L2 proficiency (phonology and lexicogrammar), and the trend becomes stronger as a function of increased input (e.g., Saito et al., 2020a, for the longitudinal relationship between auditory processing and L2 speech acquisition within the first 8 months of immersion; Saito, & Tierney, in press, for the first 4 months of immersion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation